O triste fim de Anton Kliemann: a campanha de nacionalização e seus desdobramentos no oeste de Santa Catarina - Mayer, Leandro (2016)
The purpose of this study is to investigate the repression resulting from the Nationalization Campaign in Itapiranga - commonplace place, located at the far west from Santa Catarina - during the Estado Novo period (1937-1945), using as a guide the character Antonio Kliemann a normal person arrested in 1942, accused of crimes against national security. With the implementation of the Estado Novo, Itapiranga was renumbered as "ethnic liked" in the eyes of the dictatorship Vargas because of its homogeneous ethnic background, since the colony received exclusively German-Catholic immigrants from 1926 on. For the government this area should be nationalized. In parallel, the state set up "a repressive apparatus" through the Military Brigade from Rio Grande do Sul, and ethnic and political persecutions were justified by the discourse of "construction of Brazilianness" and "nationalization of foreign". In this scenario, Antonio Kliemann, an ex-fundamentalist chief, was accused of arms smuggling and arrested, and his arrest was documented by the Criminal Case 3666 from the Court of National Security, which provides detailed information about the repressive acts committed by agents from the state in compliance with the law. Arrested, Kliemann was tortured by police officers and as a result of damage suffered he began to show mental problems. He was acquitted in 1943 by the Grand Chamber of the Court of National Security. He was diagnosed with schizophrenia and could no longer return to normal life in society and family, and in 1952, committed suicide. A sad end! For decades the oral memory keeps his history alive, as a legend, and in 1999 an act of moral and material reparations was filed in the judiciary by the family of Kliemann. Upheld in 2010 by the Supreme Court, the action is a legal precedent in the case of the Estado Novo. In 2004 Antonio Kliemann was recognized as a political amnesty post-mortem by the Amnesty Commission of the Ministry of Justice. All of this occurred in Itapiranga, place where apparently nothing happened! In theoretical and methodological terms, we work from the perspective of micro-history, and thorough analysis of two processes-crimes, central sources of the study.